Transnational Organized Crime in the Americas of the 20th century: Criminal Groups, Structure and Operation - Paredes, Gonzalo (2023)
This research work aims to have an approach to the study of transnational organized crime in the American continent in the XXI century. Based on this, the structure, functions and main characteristics of the international organized groups that are currently active in the American continent will be studied and analyzed. To achieve this, the main objective of this work is to analyze transnational organized criminal groups in the Americas of the 21st century, applying a qualitative research design using documentary and bibliographic analysis as main techniques.